PENGARUH EARNING PER SHARE, ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED TERHADAP RETURN SAHAM - Siti Hajar Karepesina; Dewa Putu Yohanes Agata L Sandopart (Jurnal Manajemen dan Bisnis, 2022)
Earnings per share (EPS), economic value added (EVA), and market value added (MVA) in relation to the rate of return of company shareholders in the consumer goods industry sector listed on the Indonesia Stock Exchange is the aim of this research. To find out how a listed Stock Exchange (IDX) will affect things from 2018 to 2020. This study uses a causal quantitative research approach. A total of 42 businesses provided data for the sample used. Documentation study and literature study were used for data collection, and descriptive statistics, classical hypothesis testing, multiple regression analysis, coefficient of determination, and parameter significance test (t-test) were used for data analysis. The research results show that EPS has a small but positive effect on stock returns.